TINJAUAN HUKUM PERDATA TERHADAP HUTANG PIUTANG TANPA PERJANJIAN TERTULIS - Martina Br Sihotang; Parlaungan Gabriel Siahaan; Noni Aulia Pratiwi; Pirhot Maranata Siburian; Sri Malem Teta Tarigan; Theresia Anggi Natama (STKIP Subang, 2026)
Debt relationships without written agreements are a common occurrence in Indonesian society, particularly in transactions based on mutual trust between creditors and debtors. However, the absence of written documents often gives rise to legal issues when disputes or defaults arise. This study aims to examine the legal standing, evidentiary weight, and legal risks of debt agreements entered into without written agreements from the perspective of Indonesian civil law. This study uses a normative legal method with a statute approach and a conceptual approach through a literature review of primary legal materials such as the Civil Code, the HIR, and the ITE Law, as well as secondary legal materials in the form of books, scientific journals, and the opinions of legal experts. The results indicate that debt agreements without written agreements remain valid and legally binding if they meet the four requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. However, the main weakness lies in the evidentiary aspect due to the lack of strong written evidence. Creditors must rely on alternative evidence such as testimonies, confessions, or electronic evidence, which are far less certain. Other risks include uncertainty about the content of the agreement, the potential for abuse, and lengthy and costly litigation. Therefore, drafting a written agreement in the form of a private deed or an authentic deed before a notary is highly recommended for greater certainty and legal protection for the parties.